A case of nivolumab-associated colitis, which relapsed after mucosal healing and was then successfully treated with mesalazine. Issue 1 (2nd January 2019) - Kikuchi, Hidezumi; Sakuraba, Hirotake; Akemoto, Yui; Murai, Yasuhisa; Fukutoku, Yukari; Asari, Taka; Tatsuta, Tetsuya; Hasui, Keisuke; Hiraga, Hiroto; Sawaya, Manabu; Chinda, Daisuke; Mikami, Tatsuya; et al.
Abstract: Currently, the number of patients treated with immune-checkpoint inhibitor involving nivolumab is increasing. Nevertheless, it causes various immune-related adverse events (irAEs). Here, we report the case of a patient who underwent long-term follow-up after suffering from nivolumab-associated colitis. The patient was a 57-year-old man who underwent resection of a bladder tumor. Following surgery, lymph node metastasis was detected, and he was treated by nivolumab. Two months after treatment with nivolumab, the patient complained of bloody diarrhea. Colonoscopy revealed pancolitis with erosions, loss of vascular pattern and erythema. Pathological findings indicated a disease state of pan-ulcerative colitis. As an irAE by nivolumab, the patient was started with 30 mg of prednisolone. Prednisolone treatment successfully induced clinical remission and mucosal healing. Nevertheless, eight months after stopping the steroid treatment, the colitis relapsed with diarrhea following elevation of fecal immunochemical test (FIT) and fecal calprotectin (CPT). The relapsed colitis was treated by mesalazine, and then diarrhea was improved. Nivolumab-associated colitis relapsed following mucosal healing suggesting that it is necessary to consider maintenance therapy as well as remission induction for long-term survivor. The present case also demonstrates that the FIT and CPT would be effective biomarker to assess the disease activity of nivolumab-associated colitis.